2009
DOI: 10.5174/tutfd.2009.01700.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification Of Candida Species From Blood Cultures With Fluorescent In Situ Hybridization (fish), Polymerase Chain Reaction-restriction Fragment Length Polymorphism (pcr-rflp) And Conventional Methods

Abstract: Objectives: Rapid and accurate identification of Candida species from blood cultures is crucial to ensure effective antifungal therapy and to reduce the morbidity and mortality associated with bloodstream fungal infections. In this study, we aimed to identify Candida spp. from blood culture samples with fluorescent in situ hybridization (FISH), polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and conventional methods. Materials and Methods:A total of 50 yeast positive samples out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Other molecular methods, such as fluorescent in situ hybridization (FISH), have been described both as quick and accurate. 24 However, utilizing FISH requires that each species needing identification has its own unique probe as well as preparing the sample in such a way that the probe can enter the cell and a culture step to generate enough sample to work with. Because our method does not require large numbers of cells and is a label-free method, it may be usable on a minimally processed clinical specimen, perhaps even as a point of care diagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…Other molecular methods, such as fluorescent in situ hybridization (FISH), have been described both as quick and accurate. 24 However, utilizing FISH requires that each species needing identification has its own unique probe as well as preparing the sample in such a way that the probe can enter the cell and a culture step to generate enough sample to work with. Because our method does not require large numbers of cells and is a label-free method, it may be usable on a minimally processed clinical specimen, perhaps even as a point of care diagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one specimen, FISH method detected C. parapsilosis , whereas the conventional method misidentified it as C. glabrata . [63,64] It was later confirmed with repeated culture methods that detected Candida spp . was C. parapsilosis as correctly identified by FISH method.…”
Section: Detection Of Candidamentioning
confidence: 92%
“…The specificity and sensitivity of PNA FISH Flow probes for Candida identification were 100% (49 of 49) and 100% (101 of 101) respectively and the whole staining process completed in 1 h.[61] Gherna et al also used the PNA FISH detection kit from AdvanDX and identified C. albicans and C. glabrata from 40 positive blood culture bottles in 1.25 h.[62] In another report, FISH oligonucleotide probes, labeled with fluorescein isothiocyanate (FITC; green signal) and fluorochrome CY3 (red signal), were synthesized by Microsynth (Switzerland, Table 2). [63,64] Candida was detected in 98% of positive blood samples (49 of 50) with PF2 all yeast probe. Different Candida spp .…”
Section: Detection Of Candidamentioning
confidence: 99%
See 1 more Smart Citation